Homespun gospel : the triumph of sentimentality in contemporary American evangelicalism - Brenneman, Todd M., 1975- (Oxford ; New York : Oxford University Press, 2014)
In popular evangelical literature, God is loving and friendly, described in heartfelt, often saccharine language that evokes nostalgia, comfortable domesticity, and familial love. This emotional style has been widely adopted by the writers most popular among American evangelicals, including such celebrity pastors as Max Lucado, Rick Warren, and Joel Osteen. Todd M. Brenneman provides groundbreaking insight into the phenomenon of evangelical sentimentality: an emotional appeal to readers' feelings about familial relationships, which can in turn be used as the basis for a relationship with God. Brenneman shows how evangelicals use tropes of God as father, human beings as children, and nostalgia for an imagined idyllic home life to provide alternate sources of social authority, intended to help evangelicals survive a culture that is philosophically at odds with conservative Christianity. Yet Brenneman also demonstrates that the sentimental focus on individual emotion and experience can undermine the evangelical agenda. Sentimentality is an effective means of achieving individual conversions, but it also promotes a narcissism that blinds evangelicals to larger social forces and impedes their ability to bring about the change they seek. --From publisher's description
God's in the business of giving mulligans : sentimentality and therapeutic culture -- You are special : the anti-intellectualism of sentimental evangelicalism -- "New York Times best-selling author" : Christian media and the marketing of sentiment -- America looks up : sentimentality, politics, and American evangelicalism.
Includes bibliographical references (pages 163-191) and index.
Keywords: Evangelicalism -- United States -- History -- 20th century; Evangelicalism -- United States -- History -- 21st century; Sentimentalism; Emotions -- Religious aspects -- Christianity; United States -- Church history -- 20th century; United States -- Church history -- 21st century; Emotions -- Religious aspects -- Christianity; Evangelicalism; Sentimentalism; United States; Evangelikale Bewegung; 2; USA; 1900 - 2099; Church history; History